World Economic and Financial Surveys : International Capital Markets, 1992. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1992)
This paper presents the IMF's annual survey of developments, prospects, and key policy issues in international capital markets. It focuses on how to manage the restructuring of capital markets in an environment of wide-ranging liberalization, intense competition, and growing securitization-in a way that avoids a systemic crisis as well as moral hazard risks and budgetary costs associated with public sector support of weak financial institutions. A key feature of the new financial environment is the competition-driven disintermediation from banking systems-particularly from wholesale banking-into securitized money and capital markets. The more creditworthy corporate borrowers in major industrial countries are increasingly able to satisfy their liquidity, risk-management, and financing needs directly in liquid securities markets. Securitization is forcing adjustments across the entire spectrum of activities and institutions in financial markets. The loss of traditional balance sheet business has led to cost cutting and to consolidation in the wholesale banking sector and to an expansion in off-balance sheet activities, including backup lines of credit and forward interest rate and foreign exchange contracts.